Acceptability for COVID-19 vaccination: perspectives from Muslims - Li Ping Wong; Haridah Alias; Megat Mohamad Amirul Amzar Megat Hashim; Hai Yen Lee; Sazaly AbuBakar; Ivy Chung; Zhijan Hu; Yulan Lin (Taylor & Francis Group, 2022)
This study aims to assess COVID-19 vaccine acceptance among Muslims in Malaysia. A cross-sectional internet-based survey was to determine acceptance of COVID-19 vaccine. Other influential factors, namely socio-demographics, COVID-19 experience, self-perceived level of religiosity, support in immunization, COVID-19 immunization attitudes, and health fatalistic beliefs (measured using the Helpless Inevitability Subscale of the Religious Health Fatalism Questionnaire, RHFQ-HI) were investigated. The majority reported a definite intent to receive the COVID-19 vaccine (57.3%; 95% CI 55.0-59.6) followed by a probable intent (42.7%; 95% CI 40.4-45.0%). COVID-19 immunization attitudes measured by attitudinal barriers to vaccination scores were found to be the strongest influence of COVID-19 vaccination intent, whereby participants who have lower attitudinal barrier scores reported higher COVID-19 vaccination intent (OR = 6.75 ; 95% 5.20-8.75). Although religious health fatalism was not significantly associated with vaccination intent, a significantly higher proportion of participants with score 4-9 (61.9%) in the RHFQ-HI reported intent to receive COVID-19 vaccine than those with a score of 10-20 (53.5%), p < .001. Intervention for people with skeptical attitudes toward COVID-19 vaccination is warranted.